Karakteristik Kubangan dan Aktivitas Berkubang Babi Hutan (Sus scrofa L.) di Hutan Pendidikan dan Penelitian Biologi (HPPB) Universitas Andalas - Wido Rizki Albert; - Rizaldi; Jabang Nurdin (Universitas Andalas, 2014)
Wallowing activity is thought to have some important roles in the viability of wild boars (Sus scrofa L.). The characteristics of wallow and wallowing activity can show the ability of the boars to adapt with variety environmental challenges. Study on the characteristics of wallow and wallowing activity of the boars at the Biological Education and Research Forest (HPPB) Andalas University was conducted from September to December 2012 and from April to July 2013. This study was conducted by observing the characters of five wallows, while wallowing activities at two different wallows were observed by using camera traps. The results showed that wallows were found mainly rounded in shape, located near by habitual animal path with shadowed by dense canopy. The dominant substrate of wallows is particles of gravel and coarse sand. The rubbing trees were found around the wallows. From a total 197 observation days, we found 53 video and 51 photos which indicated the wallowing activities within 26 different visiting times. Those activities occurred in the morning between 6:00 am to 09:00 am, with the temperature around the wallows was 25⁰ C. Activities performed while wallowing is rolling, standing, resting and rooting. The result of this study may suggest that wallowing activity has more important function than thermoregulation as previously suggested.Keywords: wild boar, characteristics wallow, wallowing activity, thermoregulation.